Real-Time Lightweight Monitoring System for 5G Standalone Networks Using MQTT and Node-RED - Muhammad Juan Farza Rafly Alganiyu; Sopian Soim; Mohammad Fadhli (Universitas Medan Area, 2026)
The rapid development of 5G Standalone networks requires a monitoring system capable of operating in real time while maintaining efficient computational resource utilization. This study aims to design and implement a lightweight monitoring system based on Message Queuing Telemetry Transport and Node-RED for a Universal Software Radio Peripheral B210-based 5G Standalone infrastructure. The proposed system applies a publish/subscribe communication architecture in which telemetry data are distributed through Message Queuing Telemetry Transport and visualized using a Node-RED dashboard interface. The research environment utilizes Open5GS and srsRAN to generate and monitor network parameters in real time. The results demonstrate that the developed monitoring system is capable of displaying telemetry information responsively with stable data transmission performance and low computational overhead. In addition, the lightweight telemetry architecture successfully supports centralized monitoring without significantly affecting the operational performance of the main system. Therefore, the proposed approach can be considered an effective alternative solution for supporting efficient and real-time operational monitoring in Software Defined Radio-based 5G Standalone environments